Short-term functional outcome after fast-track primary total knee arthroplasty: analysis of 623 patients - Egmond, Jeroen C Van; Hesseling, Brechtje; Verburg, Hennie; Mathijssen, Nina M C (Acta Orthopaedica, 2021)
Background and purpose — Early functional outcome after total knee arthroplasty (TKA) has been described before, but without focus on the presence of certain func- tional recovery patterns. We investigated patterns of func- tional recovery during the first 3 months after TKA and determined characteristics for non-responders in functional outcome. Patients and methods — All primary TKA in a fast- track setting with complete patient-reported outcome mea- sures (PROMs) preoperatively, at 6 weeks, and 3 months postoperatively were included. Included PROMs were Oxford Knee Score (OKS), Knee disability and Osteoarthritis Outcome Score Physical Function Short-Form (KOOS-PS), and EuroQol 5 dimensions (EQ-5D) including the self-rated health Visual Analogue Scale (VAS). Patients with improve- ment on OKS less than the minimal clinically important dif- ference (MCID) were determined as non-responders at that time point. Characteristics between groups of responders and non-responders in functional recovery were tested for differ- ences: we defined 4 groups a priori, based on the responder status at each time point. Results — 623 patients were included. At 6 weeks OKS, KOOS-PS, and EQ-5D self-rated health VAS were statis- tically significant improved compared with preoperative scores. The mean improvement was clinically relevant at 6 weeks for KOOS-PS and at 3 months for OKS. Patient char- acteristics in non-responders were higher BMI and worse scores on EQ-5D items: mobility, self-care, usual activities, and anxiety/depression. Interpretation — Both statistically significant and clin- ically relevant functional improvement were found in most patients during the first 3 months after primary TKA. Pre- sumed modifiable patient characteristics in non-respond- ers on early functional outcome were BMI and anxiety/ depression.